INDONESIAN ENGLISH AS A FOREIGN LANGUAGE LEARNERS’ INTERPERSONAL COMMUNICATION: PROFILES AND CHALLENGES - Menggo, Sebastianus; Jama, Karolus Budiman; Adnyani, Ni Luh Putu Sri; Krismayani, Ni Wayan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This research addresses interpersonal communication abilities and the related challenges faced in English as a Foreign Language (EFL) classrooms within Indonesian university settings. Knowledge of interpersonal communication influences how EFL learners perform in educational environments that require direct interaction. This study aims to explore students’ interpersonal communication abilities in speaking classes and the challenges they encounter. A cross-sectional survey was conducted between June and July 2023, involving 315 college students from six English Study Programs at six universities across three Indonesian provinces. Data were collected using questionnaires and interviews, followed by quantitative analysis. The findings indicate that the respondents’ interpersonal communication profiles were classified as Moderate (Average = 3.26). The most prevalent challenge (Average = 4.6) in developing interpersonal communication skills during speaking courses was difficulty in understanding the pronunciation of their speech partners. These findings are significant for undergraduate students, as they highlight the importance of developing communication skills through communicative competence. EFL learners are encouraged to communicate effectively by focusing on both the micro and macro components of linguistics. These elements are essential to cultivating a more compassionate, dynamic, engaging, functional, and experiential language learning environment, as they complement each other.